Reflective and ruminative processing of positive emotional memories in bipolar disorder and healthy controls - Gruber, June (2009)
Recent evidence suggests that reflective (i.e., distanced-why), as compared to ruminative (i.e., immersed-why), processing of negative memories is associated with reductions in negative affect. The present study extended this line of work by examining the effect of these two processing conditions on positive memories among persons with bipolar disorder (BD; n = 27) and a healthy control group (CT; n = 27). After a resting baseline period, participants were instructed to recall a happy autobiographical memory. Using a within-subjects design, participants were asked to process the happy memory in two different experimental conditions (reflective, ruminative) while their experiential, behavioral, and autonomic responses were measured. Consistent with hypotheses, reflective processing was associated with lower self-reported positive affect, positive thoughts, and heart rate compared to ruminative processing for all participants. When current symptoms were controlled for, BD participants reported greater positive affect across both conditions relative to CT participants. Prospective studies are needed to test the extent to which processing of positive emotion contributes to the course of symptoms in bipolar disorder.